Gekko Saves the City - Nakamura, May (New York : Simon Spotlight, 2018)
When Romeo turns Gekko's pet lizard, Lionel, into a huge monster, it's up to the PJ Masks to save the city.
Based on the episode "Lionel-saurus"
Keywords: Superheroes -- Juvenile fiction; Lizards -- Juvenile fiction; Readers (Primary)